Women and men in the Fourth Gospel: a genuine discipleship of equals - Beirne, Margaret M. (Journal for the study of the New Testament, 2003)
The fourth gospel presents the reader with an early christian text in which women and men are treated as a discipleship of equals as this term is broadly understood in the work of Elisabeth Schussler Fiorenza but qualified with respect to her discussion of the meaning of 'equality' when applied to gender. Specifically, the gospel contains six examples of gender pairs of characters (a widely-accepted lukan feature). The members of each pair are portrayed in a parallel or contrasting faith encounter with the Johannine Jesus which is of substantial theological importance to the gospel's stated pu